Fever and clinical thermometry: What do physicians and nurses really know? - Neves, Catarina (2019)
Introduction: Fever is a leading cause of Pediatric visits. However, most studies used as reference for fever assessment had a cross-sectional design and were conducted in adults. Different and more precise fever definitions exist within the field of knowledge known as clinical thermometry. Aims: To assess basic knowledge of health professionals working in Pediatrics regarding fever physiopathology and clinical thermometry. Material and Methods: A cross-sectional analytical study was performed between February and July 2014 through application of an anonymous closed-end questionnaire to health professionals. Results: From 426 questionnaires applied, 29% were completed by nurses and 71% by physicians. Within the whole group, 89% did not know how human “normal temperature” was determined, 70% did not recognize the “individual definitions” of fever, 33% acknowledged a “subfebrile” status, 39% did not recognize the most and least accurate anatomical sites for temperature measurement, and 57% did not recognize the dynamic difference between core and peripheral temperatures. Hyperthermia and fever definitions were confounded by 78% of nurses and 56% of physicians. Conclusions: Most health professionals surveyed had a limited knowledge of fever and clinical thermometry. The traditional oversimplification of this subject can lead to underestimation of true febrile statuses.